Optimal Hematoma Volume Cut Points to Predict Functional Outcome After Basal Ganglia and Thalamic Hemorrhages - Nakagawa, Kazuma; King, Sage L.; Seto, Todd B. (Frontiers in Neurology, 2018)
Background Basal ganglia hemorrhage (BG-ICH) and thalamic hemorrhage (TH-ICH) have been historically grouped into a single “deep” hemorrhage group in prior studies. We aimed to assess whether BG-ICH and TH-ICH have different optimal hematoma volume cut points in predicting functional outcome. Methods Patients with BG-ICH and TH-ICH with no preexisting disabilities who were enrolled in a single-center intracerebral hemorrhage (ICH) cohort study were studied. The hematoma volume of patients who achieved modified Rankin Scale (mRS) of ≤2 and ≤3 at 3 months were compared between BG-ICH and TH-ICH groups. Receiver operating characteristic (ROC) curves were created to determine the optimal hematoma volume cut points in predicting 3-month mRS of ≤2 and ≤3 for BG-ICH and TH-ICH groups. Results A total of 135 (81 BG-ICH and 54 TH-ICH) patients were studied. The hematoma volume among those with 3-month mRS ≤ 2 (BG-ICH: 9.5 ± 5.4 cm3 vs. TH-ICH: 5.1 ± 4.9 cm3, p = 0.01) and 3-month mRS ≤ 3 (BG-ICH: 14.2 ± 13.4 cm3 vs. TH-ICH: 4.7 ± 4.1 cm3, p = 0.001) were smaller in TH-ICH than BG-ICH. The area under the ROC curve in predicting mRS ≤ 2 was 0.838 for BG-ICH (optimal hematoma volume cut point: 18.0 cm3, sensitivity 72.1%, specificity 95.0%) and 0.802 for TH-ICH (optimal hematoma volume cut point: 4.6 cm3, sensitivity 83.8%, specificity 70.6%); and in predicting mRS ≤ 3 was 0.826 for BG-ICH (optimal hematoma volume cut point: 28.8 cm3, sensitivity 71.4%, specificity 93.8%) and 0.902 for TH-ICH (optimal hematoma volume cut point: 5.5 cm3, sensitivity 92.9%, specificity 76.9%). Conclusion TH-ICH have smaller optimal hematoma volume cut points than BG-ICH in predicting functional outcome.